Changing Pattern of Acute Coronary Syndrome, the Burden Shifting Towards Younger Age Group (Medical Forum Monthly, 2020)
Objective: To determine the frequency of Acute coronary syndrome in young age group among patients admitted to Coronary Care Unit (CCU).Study Design: Descriptive / observational studyPlace and Duration of Study: This study was conducted at the Coronary Care Unit (CCU), Saidu Teaching Hospital, Saidu Sharif, Swat from November 2018 to May 2019.Materials and Methods: This was a hospital based study, CCU admission data from June 2017 to April 2018 was reviewed and all patients admitted with diagnosis of ACS were identified, young age group was defined as 45 years or less. Total number of patients was 1327.The data of these patients was then recorded on a pre-design profarma, and then analyzed on SPSS for age, gender, and type of ACS.Results: Data was available on 1327 patients admitted with ACS. 741(55.8%) were male and 586 (44.2%) were female. The age range of these patients was from 15 to 120 years, with mean of 60.21±13.2 years. 196 patients (14.8 %) were in younger age group, while 1131 (85.2%) patients were more than 45 years old. Patients in 50 years or below age group were 26.5%. In the young age group who were admitted with ACS 3.6% patients were 35 years or below, 0.5% were 25 years or below, while only one patient was 15 years old. Among the young patients 99 (51.3%) were male and 97 (48.7%) were female.30 were admitted with UA, 48 with NSTEMI, while 118 patient had STEMI. Among these patients 55 had Anterior wall MI, 55 had inferior wall MI, while 8 had lateral wall MI.45 patients (23%) in young age group were diabetic and 151(77%) were non-diabetic.Conclusion: Acute coronary syndrome is common in young age group in our population as compared to the developed countries, which need further work to identify the risk factors in our population and adapt measure to stop this catastrophe.